MOTIVASI BELAJAR DAN HASIL BELAJAR PSIKOMOTOR SISWA MTs SUNAN AMPEL SIMAN KEPUNG KELAS IX DALAM AKTIVITAS PRAKTIKUM IPA - Dwi Kameluh Agustina (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
This study describes how motivation promotes psychomotor learning outcomes of MTs students.  The objectives of this study are to see (1) learning motivation in practicum activities of sciences subject, and (2) psychomotor learning achievement in the practicum of sceince subject.  This study used descriptive design assigning grade IX of 34 students of MTs Siman Kepung Blitar as sample. Data were collected using questionnair and test.  Data were analyzed using descriptive statistics.  The study found that students average motivation is 83% indicating high motivation and good performance.  Rate percentage of motivation in each category is as follows: (1) interest 90% or good, (2) attention 86% very good, (3) focus of concentration 78% good, and (4) diligent 80% good. Average scor of psychomotor achievement is 80 or very good.